Pengaruh Pemberian Tablet Ekstra Ikan Gabus dengan Proses Penyembuhan Jahitan Luka Post SC - Nita Safitri; Qomariyah Qomariyah; Kristina Maharani (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
A Caesarean section, or C-section, is a surgical procedure where a baby is delivered through an incision made in the mother’s abdomen and uterus. To aid the healing of post-Caesarean wounds, mothers need not only antibiotics but also a diet that provides high-quality nutrition and adequate calories. The research question being investigated is: "Do Age, Parity, Education, and Occupation Affect the Healing Process of Post-Caesarean Wound Stitches?" This study uses a quasi-experimental design with a Post-test Only Control Group Design. The study population includes mothers who had a C-section at Pemalang Hospital. Participants were divided into two groups: 49 received catfish extract tablets (the experimental group), and 49 received standard wound care (the control group). Sampling was conducted using purposive sampling techniques. Data were analyzed through both univariate and bivariate methods. The results showed a p value of 0.000 for the experimental group and 0.046 for the control group (both p values < 0.05), indicating that catfish extract tablets significantly influence the healing process of post-Caesarean wound stitches..